Capital's Utopia Vandergrift, Pennsylvania, 1855-1916 - Mosher, Anne E. (Johns Hopkins University Press, 2004)
In the 1890s the Apollo Iron and Steel Company ended a bitterly contested labor dispute by hiring replacement workers from the surrounding countryside. To avoid future unrest, however, the company sought to gain tighter control over its workers not only at the factory but also in their homes. Drawing upon a philosophy of reform movements in Europe and the United States, the firm decided that providing workers with good housing and a good urban environment would make them more loyal and productive. In 1895, Apollo Iron and Steel built a new, integrated, non-unionized steelworks and hired the nation's preeminent landscape architectural firm (Olmsted, Olmsted, and Eliot) to design the model industrial town: Vandergrift.In Capital's Utopia: Vandergrift, Pennsylvania, 1855-1916, Anne E. Mosher offers the first comprehensive geographical overview of the industrial restructuring of an American steelworks and its workforce in the late nineteenth-century. In addition, by offering a thorough analysis of the Olmsted plan, Mosher integrates historical geography and labor history with landscape architectural history and urban studies. As a result, this book is far more than a case study. It is a window into an important period of industrial development and its consequences on communities and environments in the world-famous steel country of southwestern Pennsylvania.